2016
DOI: 10.17230/ecos.2016.43.1
|View full text |Cite
|
Sign up to set email alerts
|

Managerial efficiency and failure of U.S. commercial banks during the 2007-2009 financial crisis: was this time different?

Abstract: Eficiencia en la gestión y quiebra de bancos comerciales estadounidenses durante la crisis financiera de 2007-2009: ¿fue diferente esta vez?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The loan quality variable had =-0.06, p-value 0.15, which was a negative relationship but statistically insignificant. Alvarez-Franco and Restrepo-Tobon (2016) observe that loan quality is an important pointer to bank survival and argue that less diversified banks are more likely to fail due to dependence on interest income. Huang et al (2012) study found p-value for ASEAN at -0.156; G8 -0.859, EU at -1.253, NIC at -0.086 and G-20 at -0.258 all being significant at 5% level that is p-value<0.05 and concluded that net interest income predicted the financial distress of global banks best.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loan quality variable had =-0.06, p-value 0.15, which was a negative relationship but statistically insignificant. Alvarez-Franco and Restrepo-Tobon (2016) observe that loan quality is an important pointer to bank survival and argue that less diversified banks are more likely to fail due to dependence on interest income. Huang et al (2012) study found p-value for ASEAN at -0.156; G8 -0.859, EU at -1.253, NIC at -0.086 and G-20 at -0.258 all being significant at 5% level that is p-value<0.05 and concluded that net interest income predicted the financial distress of global banks best.…”
Section: Discussionmentioning
confidence: 99%
“…These losses normally emanate from long periods of asset quality deterioration due in part to excessive credit expansion. -Franco and Restrepo-Tobon (2016) state that during and immediately after 2007-2009 US financial crisis three hundred twenty-two (322) US Commercial banks failed with an estimated loss of USD 86 billion to the FDIC compared to the period 1980-1989 when one thousand four hundred sixty-seven (1467) banks failed with an estimated cost of $62 billion and to the period 1990-1999, four hundred thirty-six (436) banks failed with estimated loss of $7 billion. Cleary and Hebb (2016) state that the FDIC fund went into the red during 2009 and that is a confirmation of the severity of bank distress.…”
Section: Introductionmentioning
confidence: 99%
“…This will help the regulators in fashioning laws and guidelines for the industry players. According to Alvarez-Franco and Restrepo-Tobon (2016), financial performance evaluation is critical to both the regulator and managers of the banks.…”
Section: Introductionmentioning
confidence: 99%